THE EFFECT OF CAREER DEVELOPMENT, NON-FISCAL WORK ENVIRONMENT AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE LOYALTY OF THE SUNGAI PENUH CITY REGIONAL PLANNING AND DEVELOPMENT AGENCY - Suhelmi Helia; Roli Eko Purnama; Safriwan Safriwan; Rian Naveria; Aminur Aminur (SEAN Institute, 2022)
This study aims to see the influence of (1) How does career development affect the loyalty of employees of the Sungai Penuh City Bappeda? (2) How does the non-physical work environment affect the loyalty of employees of the Sungai Penuh City Bappeda? (3) How does the organization's commitment affect the loyalty of employees of the Sungai Penuh City Bappeda. (4) How does career development, non-physical work environment, and organizational commitment together affect the loyalty of employees of the Sungai Penuh City Bappeda? The population in this study was 60 employees of the Sungai Penuh City Bappeda. And the technique of determining the number of samples taken as respondents using total sampling in Sugiyono (2017) The results of this study show that (1) Career development has a positive significant influence on the performance of Bapedda employees in Sungai Penuh City (2) Non-physical work environment has a positive influence on the performance of Bapedda employees in Sungai Penuh City (3) Organizational commitment has a positive influence on performance . employees of Bapedda Kota Sungai Penuh (4) Career development, Non-physical work environment and Organizational commitment together positively affect the loyalty of Bapedda employees of Sungai Penuh City